Phytomonitoring Of Harmful Insects On Nut Plantations In Uzbekistan - Umurzakov E.U; Pulatov O.A; Kholova S.N (Genius Publishing Group, 2021)
The article provides information on the distribution and development of lush bulbs in the mountain and foothills of Samarkand and Kashkadarya regions. Bioecology of pests, such as big nuts in natural and cultivated walnuts and small walnuts.
Keywords: Greens; pests; walnuts; bioecology